2009
DOI: 10.1080/10428190903131755
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of dailyversusweekly administration of 2-chlorodeoxyadenosine in patients with hairy cell leukemia: a multicenter phase III trial (SAKK 32/98)

Abstract: Daily administration of 2-chlorodeoxyadenosine (Cladribine, CDA) is a standard treatment for hairy cell leukemia, but may cause severe neutropenia and neutropenic fever. This trial compared toxicity and efficacy of weekly versus daily CDA administration. One hundred patients were randomized to receive standard (CDA 0.14 mg/kg/day day 1-5 [Arm A]) or experimental treatment (CDA 0.14 mg/kg/day once weekly for 5 weeks [Arm B]). The primary endpoint was average leukocyte count within 6 weeks from randomization. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…The initial response rate with the first course of cladribine was 97.3%, and the majority of responses were complete responses (80.7%). The results reported confirm previous observations that cladribine administered to patients with HCL induces high response rates [9,[15][16][17][18][19][20][21][22]. In 1998, Saven et al [17] obtained a CR in 91% of their patients and a PR in 7% in the first treatment with cladribine, and reported relapse in 26% of them in a median time of 29 months, a CR in 62% and a PR of 26% in their second use of cladribine, in their study evaluating the results in 358 HCL patients treated with cladribine.…”
Section: Discussionsupporting
confidence: 90%
“…The initial response rate with the first course of cladribine was 97.3%, and the majority of responses were complete responses (80.7%). The results reported confirm previous observations that cladribine administered to patients with HCL induces high response rates [9,[15][16][17][18][19][20][21][22]. In 1998, Saven et al [17] obtained a CR in 91% of their patients and a PR in 7% in the first treatment with cladribine, and reported relapse in 26% of them in a median time of 29 months, a CR in 62% and a PR of 26% in their second use of cladribine, in their study evaluating the results in 358 HCL patients treated with cladribine.…”
Section: Discussionsupporting
confidence: 90%
“…Selected publications are summarized in Table 2. 25, 26, 32, 33, 34, 35, 36, 37, 38 A single course of therapy corresponding to a duration of 5–7 days is already able to achieve complete remissions with durable responses: ORR of 87–100% 14, 39, 40 and CRR of 85-91% 39, 40 have been reported. The 5-year progression-free survival (PFS) rates vary between 72–84% and the OS at 12 years vary between 75–87%.…”
Section: Treatment Options Results and New Insightsmentioning
confidence: 99%
“…A second prospective randomized trial compared cladribine, 0.14 mg/kg, for 5 daily doses with 5 weekly doses. 23 In this Swiss study of 100 patients, no significant differences were found in rates of grade 3 to 4 neutropenia (90% vs 80%), infection, or hospitalization within 10 weeks from treatment. The overall best response rate was 86% in both groups.…”
Section: Alternative Methods Of Administrationmentioning
confidence: 98%